Pemanfaatan Data Mining Menggunakan Metode K-Means Untuk Analisa Komoditas Telur Ayam - Muhammad Faisal; Suharmanto; Wiranti Sri Utami; Nila Pratiwi (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
Chicken eggs are a source of animal protein that taste delicious and have many benefits, especially in the culinary field or are one of the main ingredients in making cakes. Some animals, especially poultry, can produce eggs that can be bought and sold and consumed by humans, including chicken eggs, duck eggs, puyu eggs and goose eggs, but the most popular and frequently consumed by humans are chicken eggs. There are two types of chicken eggs, namely free-range chicken eggs (Buras) and free-range chicken eggs (Ras). Data on broiler egg commodities is recorded at the Central Statistics Agency (BPS) and this data can be used for research, especially in the field of data mining using the K-clustering method. The aim of the facility is to determine the commodity cluster for purebred chicken eggs in each province. The number of clusters obtained from 34 provinces was 8 clusters With a cluster percentage of 76,6%.